Development of Time- and Energy-Resolved Synchrotron-Radiation-Based Mössbauer Spectroscopy. Issue 1 (1st December 2022) - Kitao, S.; Masuda, R.; Fujihara, T.; Tajima, H.; Nagasawa, N.; Yoda, Y.; Masuda, T.; Yoshimura, K.; Seto, M.
Abstract: Synchrotron-radiation based Mössbauer spectroscopy has become a useful technique capable for investigating various Mössbauer isotopes. For a typical experimental setup, the information associated with the pulse height (that is, energy) in an avalanche photodiode (APD) detector has not been used effectively. By using a system for simultaneous measurement system of time and energy associated with the APD signal, a system for the time- and energy-resolved Mössbauer spectroscopy has been developed. In this system, the pulse height information was converted to the time information through an amplitude-to-time converter applied to one of the divided signals from the APD. The corresponding time information was processed separately from another one of the divided signals. Both signals are recorded by a multi-channel scaler in an event-by-event data acquisition process. The velocity information from the Mössbauer transducer was also recorded as a tag for each signal event. Thus, the Mössbauer spectra with any time- and energy-window can be reconstructed after the data collection process. This system can be used for many purposes in time- and energy-resolved Mössbauer spectroscopy, and shows significant promise for use with other fast detectors and for various types of experiments.